PELATIHAN PENGISIAN RUBRIK DAN BORANG AKREDITASI BAGI PAUD DARMA BAKTI DESA GURUH BARU KECAMATAN MANDIANGIN TIMUR KABUPATEN SAROLANGUN PROVINSI JAMBI - uying hapid alatas; Aksul Dewi Fikra; Iswandi Iswandi; Sri Utami; Henki Setiyadi; Diyan Andriani (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Early childhood education teachers are at the forefront of developing the character and abilities of children at their golden age. So that requires early childhood education teachers who are competent, especially in the field of teaching and learning. This service has the aim of increasing teacher understanding regarding the importance of filling out online rubrics and accreditation forms, and the importance of each school for accreditation. This service method consists of lecture, discussion, demonstration and direct practice methods. The importance of the results of this service is to improve the skills of PAUD teachers, especially when filling out online rubrics and accreditation forms can be carried out gradually. The importance of accreditation is to improve the quality of schools in PAUD teachers' premises. The increase in understanding and ability of early childhood teachers is very significant based on the results of the pre-test and post-test that have been distributed, which has increased in each category, such as the activity category, which has increased. Both the medium core activity category and the medium closing category. And it can be seen also with the questions and answers submitted by the teacher Keywords: skills; competencies; microteahing; kindergarten